2021
DOI: 10.3390/w13192728
|View full text |Cite
|
Sign up to set email alerts
|

Expert-Based Assessment and Mapping of Ecosystem Services Potential in the Nemunas Delta and Curonian Lagoon Region, Lithuania

Abstract: The Curonian Lagoon (SE Baltic Sea) and the coastal wetland system play a vital role in maintaining the overall cultural, economic and ecological health of the region. However, its value is still largely underestimated and there is a lack of integrated ecosystem management based on multiple ecosystem services assessment. In this study, 34 ecosystem services (ES) were identified, assessed and mapped following the Common International Classification of Ecosystem Services (CICES). Using expert opinion, 35 land co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In the work of [18], performed for the territory of the Krasnodar Territory, the number of the considered factors was 9 indicators, for landslide hazard assessment number of parameters varies from 5 for Mussoorie Township case study [19] to8 factors in the work of [20] for Indian Himalaya. The weight of each factor is set based on the expert rule approach [21][22][23][24][25][26][27][28][29]. Or weights may be calculated on the basis of cases study (In [30], statistical procedure consisted in calculating a landslide frequency per class area expressed in percentage, i.e., number of landslide pixels.km −2 × 100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of [18], performed for the territory of the Krasnodar Territory, the number of the considered factors was 9 indicators, for landslide hazard assessment number of parameters varies from 5 for Mussoorie Township case study [19] to8 factors in the work of [20] for Indian Himalaya. The weight of each factor is set based on the expert rule approach [21][22][23][24][25][26][27][28][29]. Or weights may be calculated on the basis of cases study (In [30], statistical procedure consisted in calculating a landslide frequency per class area expressed in percentage, i.e., number of landslide pixels.km −2 × 100).…”
Section: Methodsmentioning
confidence: 99%
“…The formation and interrelationship of erosion hazardous geological processes and their impact on the environment of high mountain areas are shown in Figure 3.The location of the investigated area in the zone of alpine tectonomagmatic activation of the Greater Caucasus determines the complex engineering and geological conditions inherent in the areas of alpine folding, caused by the diversity of the lithological composition of rocks, their intense tectonic disturbance, active neotectonics and seismicity, and the wide development of modern exogenous geological processes (Figure 3) [41,42]. The weight of each factor is set based on the expert rule approach [21][22][23][24][25][26][27][28][29]. Or weights may be calculated on the basis of cases study (In [30], statistical procedure consisted in calculating a landslide frequency per class area expressed in percentage, i.e., number of landslide pixels.km −2 × 100).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, we assumed a general transferability within the Cfb climate zone. A brief comparison of the Baltic ESP Matrix, with an ES potential matrix developed for the same study area [56], showed similarities, but also major differences between the matrices. Because of its focus on terrestrial systems, different ES definitions, and evaluation scale (0-5 vs. 0-100) used, we did not quantify the variations but only compared results for single ES.…”
Section: Transferability Of the Approachmentioning
confidence: 98%
“…However, ES assessment across the land-sea interface is needed to support spatial planning, to enable the ES applications for supporting the HD in general, and the deployment of blue-green infrastructure in particular [8]. Only few examples exist in which multiple ES have been spatially assessed across the land-sea interface (e.g., [55,56]). However, these integrated studies were solely based on CLC types, which include merely three marine habitats (i.e., estuaries, lagoons, and sea and ocean).…”
Section: Practical Relevence For Supporting Policy Implementationmentioning
confidence: 99%
“…Thickets of emergent aquatic vegetation also play an important environmental role in the formation of bird and mammal biological diversity as 23 species of birds nest in them [9]. A significant part of the Baltic Sea region's coastal zone is protected [10].…”
Section: Introductionmentioning
confidence: 99%